Teknik Memanggil Kaum Milenial (TMKM) untuk Modul Optimasi menggunakan Linear Programing dengan Excel Solver - Inderawati, Maria Magdalena Wahyuni; Hidayat, Trifenaus Prabu; Sugioko, Andre; Wong, Felicitas; Surya, Andre; Mekel, Bianca; Milano, Yosephan (Jurnal Pengabdian Masyarakat Charitas, 2023)
Optimization is the search for the optimal value of a problem with the help of one or more objective functions. Optimization problems are often found in everyday life and become important in the operation of a production system. The simplest optimization problem in the industrial world is solved using linear programming. Linear programming equations are made to solve optimization problems in the industrial world. In optimizing a problem, computational tools are needed to produce the optimal solution. Many computational tools are used, one of which is Excel Solver. Excel Solver is operated because many Microsoft Office users have this computing tool. Where everyone commonly uses Excel. The world of industrial Engineering needs someone who can solve optimization problems, especially since the current industrial era is getting more advanced. More skills are necessary for dealing with the Industrial Revolution 4.0 and Society 5.0, and it becomes a mandatory ability for an industrial engineer to solve this problem. Therefore, this community service activity is proposed with the topic: "Technique for Calling Millennials (TMKM) for Optimization Modules using Linear Programming with Excel Solver" to introduce optimization in the industrial world using existing optimization techniques and simple tools needed as applications in industrial engineering science. This community service activity was carried out in collaboration with Citra Blessing Tangerang High School. This activity is given to all students and teachers at SMA Citra Blessing Tangerang. The target audience for this activity is 50 participants. It is hoped that this activity can provide knowledge in the field of optimization and also provide an overview of industrial developments in the Industrial Revolution 4.0 era and in Society 5.0. Besides that, it also opens students' insights about the field of Industrial Engineering, especially opening students' insights about career prospects in the Industrial Engineering field.